Irrigation and water resources in Latin America and the Caribbean: challenges and strategies - Ringler, Claudia; Rosegrant, Mark W.; Paisner, Michael S. (International Food Policy Research Institute, 2000)
Latin America and the Caribbean are relatively well endowed with water resources. However, population growth and rapid urbanization are putting considerable pressure on water available for irrigation. Local and regional water scarcity problems are exacerbated by severe water quality problems; and wastewater is frequently used for irrigation. Moreover, prospects for new investments into irrigation development appear limited. This paper examines the factors underlying irrigation development in Latin America and the Caribbean, reviews the water supply situation, and describes trends in water demand and irrigated agriculture. The overall water management in the region is assessed, and recent trends in investments in the water sector, with a focus on large-scale irrigation systems, are analyzed. The paper concludes that in this context of accelerating demand and declining irrigation investments, new water development is not the primary solution to water resource challenges in the region. Much greater attention is needed on water policy and management reform to improve the efficiency and equity of irrigation and water supply systems.